Fans' preferences in the demon slayer series: manga vs. anime - Chong, Jia Jet (2024)
The goal of this research is to investigate the fans' preferences and the factors behind their preferences for manga and anime about the Demon Slayer series. 38 valid questionnaires were collected to analyze the fans' preferences for the two media forms and the main factors affecting their preferences through quantitative research methods. The study found that action scenes, visual and artistic style, and sound effects are the key factors of fan preferences. Anime attracts more audiences with its visual effects and sound performance, whereas manga has great narrative depth and detailed portrayal. This study uses transmedia storytelling theory as a theoretical approach to explore the differences between manga and anime in storytelling, audience interaction, technical performance, and their impact on fans' preferences. The findings show that different media forms have their advantages in meeting audience needs, providing an important reference for transmedia content production. This study also points out the limitations of the research sample and proposes to combine qualitative research with a larger sample size to understand fans' behavior more comprehensively. The research results provide significant inspiration for academia and industry to explore the impact of transmedia content on audience preferences.